Analysis of rainfall over Nasik district - MUKHERJEE, A. K.; SHYAMALA, B.; LAKSHMI, S. (MAUSAM, 1980)
The study of rainfall patterns over Satara, Pune and Ahmednagar districts indicated a definite variation in the distribution of rainfall even within a district. Hence, an attempt has been made in this paper to study in detail the distribution of rainfall over Nasik district. The daily normal rainfall and daily actual rainfall have been analysed and it has been found that during the months of July and August the district can be distinctly differentiated into two regions which have different rainfall pattern. The comparative study of wind over Bombay in relation to increase in rainfall over the western talukas suggested that the strengthening of westerlies at 850 mb over Bombay cause increase in rainfall over the western part of the district while the rainfall distribution in the eastern part under similar conditions does not show any marked increase.